2018
DOI: 10.1007/s00520-018-4383-y
|View full text |Cite
|
Sign up to set email alerts
|

Breaking bad news of a breast cancer diagnosis over the telephone: an emerging trend

Abstract: Receiving a telephone call about breast cancer diagnosis may be the norm rather than the exception in health care today. Trends in practice, as well as current best practices based primarily on expert opinion, may not provide optimal care for women diagnosed with breast cancer. Patient outcome research to guide future practice, such as the impact of modes of delivery of bad news, is urgently needed to determine appropriate patient-centered approaches for notification of breast cancer diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…(Greenhalgh et al, 2020) Systematic use of telephone in delivering health care has been acknowledged for more than 30 years in various medical interactions such as genetic counselling, delivery of screening results, smoking cessation programmes, palliative interventions and disclosing result of breast cancer workup. (Jenkins et al, 2007; McBride & Rimer, 1999; McElroy et al, 2019; Patrick‐Miller et al, 2013) The preference for telephone disclosure among patients refusing to participate in our RCT supports the heterogeneity in patients’ preferences, which are probably based on a multitude of aspects, but no research has so far investigated this. We find it likely that access to transportation, distance to hospital, impaired hearing, performance level, cognitive functioning, language skills, mental or physical comorbidity, local or personal tradition and dependency on relatives/care‐givers are likely factors, but this is an area for future research.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…(Greenhalgh et al, 2020) Systematic use of telephone in delivering health care has been acknowledged for more than 30 years in various medical interactions such as genetic counselling, delivery of screening results, smoking cessation programmes, palliative interventions and disclosing result of breast cancer workup. (Jenkins et al, 2007; McBride & Rimer, 1999; McElroy et al, 2019; Patrick‐Miller et al, 2013) The preference for telephone disclosure among patients refusing to participate in our RCT supports the heterogeneity in patients’ preferences, which are probably based on a multitude of aspects, but no research has so far investigated this. We find it likely that access to transportation, distance to hospital, impaired hearing, performance level, cognitive functioning, language skills, mental or physical comorbidity, local or personal tradition and dependency on relatives/care‐givers are likely factors, but this is an area for future research.…”
Section: Discussionmentioning
confidence: 55%
“…(Bray et al, 2018) Disclosure of bad news is challenging for patients, relatives and healthcare providers, (Bousquet et al, 2015; Dean & Willis, 2016; Schaepe, 2011) yet breaking bad news professionally is a clinical cornerstone for clinicians involved in workup of suspected malignancy. An increasing number patients receive a cancer diagnosis by telephone, (Kuroki et al, 2013; McElroy et al, 2019) but available models for delivering a cancer diagnosis were developed for in‐person conversation. (Baile et al, 2000; Kaye, 1996; Narayanan et al, 2010; Pereira et al, 2017) Furthermore, these models focus on a single visit, (Dean & Willis, 2016) while cancer workup is a process involving multiple clinical interactions with numerous opportunities to gradually prepare the patients and their family for a potential life‐limiting diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…While patients may have perceived this differently from how the diagnosis was actually delivered, a previous study reported that patients generally remember well how bad news was delivered . Other recent studies also observed that it remains common to deliver a cancer diagnosis by telephone: 18% of patients treated at the National Cancer Institute, and 25% to 50% of breast cancer patients in the United States received their diagnosis by telephone . However, patients prefer that their diagnosis is delivered during a personal conversation with the physician, during which the physician takes the time to discuss the condition and its consequences .…”
Section: Discussionmentioning
confidence: 99%
“…17 Other recent studies also observed that it remains common to deliver a cancer diagnosis by telephone: 18% of patients treated at the National Cancer Institute, and 25% to 50% of breast cancer patients in the United States received their diagnosis by telephone. 10,18 However, patients prefer that their diagnosis is delivered during a personal conversation with the physician, during which the physician takes the time to discuss the condition and its consequences. 10,17,[19][20][21] Therefore, it is not surprising that patients in PROCURE who received their diagnosis by letter or by telephone were less satisfied.…”
Section: Discussionmentioning
confidence: 99%
“…Since the COVID‐19 pandemic, there have been huge changes to most outpatient clinics 1 . World‐wide there is a greater use of telephone consultations to break bad news such as giving a breast cancer diagnosis 2 . Providing virtual care may be the new way forward 3 .…”
mentioning
confidence: 99%